Struggles over difference : curriculum, texts, and pedagogy in the Asia-Pacific - Nozaki, Yoshiko, 1956-; Openshaw, Roger; Luke, Allan (State University of New York Press, 2005)
"Struggles over Difference addresses education, schools, textbooks, and pedagogies in various countries of the Asia-Pacific, offering critical curriculum studies and policy analyses of national and regional educational systems. These systems face challenges linked to new economic formations, cultural globalization, and emergent regional and international geopolitical instabilities and conflicts. Contributors offer insights on how official knowledge, text, discourse, and discipline should be shaped; who should shape it; through which institutional agencies it should be administered; and social and cultural practices through which this should occur."--Jacket